Subcortical Volumes Differ in Parkinson’s Disease Motor Subtypes: New Insights into the Pathophysiology of Disparate Symptoms - Rosenberg-Katz, Keren; Herman, Talia; Jacob, Yael; Kliper, Efrat; Giladi, Nir; Hausdorff, Jeffery M. (Frontiers in Human Neuroscience, 2016)
Objectives: Patients with Parkinson’s disease (PD) can be classified, based on their motor symptoms into the Postural Instability Gait Difficulty (PIGD) subtype or the Tremor Dominant (TD) subtype. Gray matter changes between the subtypes have been reported using whole brain Voxel-Based Morphometry (VBM), however, the evaluation of subcortical gray matter volumetric differences between these subtypes using automated volumetric analysis has only been studied in relatively small sample sizes and needs further study to confirm that the negative findings were not due to the sample size. Therefore, we aimed to evaluate volumetric changes in subcortical regions and their association with PD motor subtypes. Methods: Automated volumetric magnetic resonance imaging (MRI) analysis quantified the subcortical gray matter volumes of patients with PD in the PIGD subtype (n = 30), in the TD subtype (n = 30), and in 28 healthy controls (HCs). Results: Significantly lower amygdala and globus pallidus gray matter volume was detected in the PIGD, as compared to the TD subtype, with a trend for an association between globus pallidus degeneration and higher (worse) PIGD scores. Furthermore, among all the patients with PD, higher hippocampal volumes were correlated with a higher (better) dual tasking gait speed (r = 0.30, p < 0.002) and with a higher global cognitive score (r = 0.36, p < 0.0001). Lower putamen volume was correlated with a higher (worse) freezing of gait score (r = −0.28, p < 0.004), an episodic symptom which is common among the PIGD subtype. As expected, differences detected between HCs and patients in the PD subgroups included regions within the amygdala and the dorsal striatum but not the ventral striatum, a brain region that is generally considered to be more preserved in PD. Conclusions: The disparate patterns of subcortical degeneration can explain some of the differences in symptoms between the PD subtypes such as gait disturbances and cognitive functions. These findings may, in the future, help to inform a personalized therapeutic approach.